2017
DOI: 10.1111/jcpe.12819
|View full text |Cite
|
Sign up to set email alerts
|

The role of leptin as a biomarker in the relationship between periodontitis and chronic migraine

Abstract: CP is prevalent in CM patients and when present it contributes to elevated serum leptin levels, independently of other confounding factors. Therefore, it seems that CP via leptin could be involved in the process of migraine chronification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…In particular, we recently found that patients with PD had 2.4-fold-increased risk for having CM [14]. In the present analysis we confirmed findings previously observed [14][15][16], in which PD is common in patients with CM (55 individuals diagnosed with PD, 58.5% of the whole sample). It has been hypothe-sized that during periodontal inflammation, pro-inflammatory mediators that are produced locally within the gingiva are disseminated systemically due to endotoxemia and, therefore, could be involved in migraine chronification by increasing neurogenic inflammation [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, we recently found that patients with PD had 2.4-fold-increased risk for having CM [14]. In the present analysis we confirmed findings previously observed [14][15][16], in which PD is common in patients with CM (55 individuals diagnosed with PD, 58.5% of the whole sample). It has been hypothe-sized that during periodontal inflammation, pro-inflammatory mediators that are produced locally within the gingiva are disseminated systemically due to endotoxemia and, therefore, could be involved in migraine chronification by increasing neurogenic inflammation [25].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, our group showed that patients with PD were more likely to have CM than those without PD [14]. We also reported that in CM patients, PD was associated with increased circulating levels of inflammatory markers such as leptin and procalcitonin [15,16].…”
Section: Introductionmentioning
confidence: 86%
“…In fact, the periodontal ulcerated and inflamed epithelium was 4.3 cm 2 in the chronic migraine group versus 0.4 cm 2 in the control group. Based on this, it is speculated that the biological plausibility behind the potential association between periodontitis and chronic migraine is mainly due to the transient entrance of inflammatory mediators into the bloodstream such as leptin or procalcitonin that could travel to cerebral blood vessels exacerbating migraine attacks, which in turn could lead to the chronification process of the disease. In the present study we observed that chronic migraineurs with periodontitis had significantly higher serum levels of IL‐6 compared with those without periodontitis and that there was a linear positive correlation between PISA and IL‐6, thus, confirming again the link between periodontitis, systemic inflammation, and chronic migraine.…”
Section: Discussionmentioning
confidence: 99%
“…In this case‐control study, patients with periodontitis were more likely to have chronic migraine than those without periodontitis (odds ratio [OR] = 2.4, 95% confidence interval [CI]:1.2 to 4.7) . In addition, few mechanistic reports suggested that periodontitis could increase circulating levels of proinflammatory markers such as leptin or procalcitonin in chronic migraine patients, hence, hypothesizing a possible role of periodontitis as a chronifying factor of migraine . Nevertheless, studies measuring the key neuropeptide CGRP to evaluate the impact of periodontitis on chronic migraine are still missing.…”
Section: Introductionmentioning
confidence: 93%
“…and P.A.). Both examiners were previously calibrated using 10 non‐study patients suffering from moderate or severe CP, and intraclass correlation coefficients for intra‐ and inter‐examiner reliability were calculated (>0.80) …”
Section: Methodsmentioning
confidence: 99%